Adat Land (Bengkok) Transition Process in Indonesian Land Law - Abdul Wahhab (Universitas Negeri Semarang, 2019)
This research aims to determine the transition of land rights from adat land village (bengkok) and the efforts made to provide legal protection for the people who control the land from the crooked land, this research using empirical juridical approach, using primary data and secondary data later analyzed using qualitative data analysis. This study shows that the transition process bengkok land Mutih Wetan village performed until the discharge stage by way of village meetings by providing replacement land. Soil removal procedure performed by Demak Regent Regulation No. 1 of 2011 On Guidelines For Financial Management And Wealth Village, efforts are being made to the legal protection for the people who control the land from the bengkok land village is recording the village administration to mutation associated land, forming the draft village regulations, as well as performed permit change agricultural land into land non-agricultural land rights petition efforts undertaken by the Government of Mutih Wetan village. It can be concluded that the process of transition crooked land done by the release of land by way of village meetings to provide replacement land, efforts are being made to the legal protection for the people who control the land from the bengkok land is recording the administration of the village on the mutation of land, the establishment of the draft regulation village, and the license permit change agricultural land into non-agricultural land as a condition for the right to land use certificate issuance.